Magnetocardiograph as a noninvasive and radiation-free diagnostic device for myocardial infarction: a systematic review and meta-analysis - Yansong Xu; Xiaole Han; Mingyue Guo; Ruochuan Li; Yiming Dong; Jiaxin Fan; Xiaofei Yin; Fei Xie; Jiaojiao Pang; Yuguo Chen (Emergency and Critical Care Medicine)
Abstract. Background. This study aimed to evaluate the diagnostic accuracy of magnetocardiograph, a relatively new noninvasive device, in patients with myocardial infarction (MI). Methods. To identify studies assessing the diagnostic accuracy of magnetocardiography for MI, we searched four databases on November 7, 2022, the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and Web of Science, plus ClinicalTrials.gov. Three reviewers screened the studies independently and emailed the authors for more precise data when necessary. The Quality Assessment of Diagnostic Accuracy Studies 2 tool was used to evaluate the quality of the included studies. STATA (version 17; Stata Corporation, College Station, TX, USA) was used for meta-analysis of 2 × 2 contingency table data. Results. A total of 6 articles were included in this study. The diagnostic parameters of all included studies were summarized as follows: the pooled sensitivity was 0.91 (95% confidence intervals [95% CIs]: 0.81–0.96; I2 = 88.54); specificity was 0.83 (95% CI: 0.75–0.89; I2 = 83); positive likelihood ratio was 5.3 (95% CI: 3.5–8.2); negative likelihood ratio was 0.1 (95% CI: 0.04–0.24); and diagnostic odds ratio was 51 (95% CI: 16–161). The area under the curve for the receiver operating characteristic curve was 0.92 (95% CI: 0.89–0.94). After metaregression analysis, we found that the number of channels and the way of environmental magnetic noise elimination were heterogeneous sources. Conclusion. In summary, our meta-analysis shows that magnetocardiography holds a high accuracy in diagnosing MI and takes the advantages of noninvasive, radiation-free, and noncontact. However, further high-quality studies to confirm its usefulness in diagnosing MI are warranted.